1994
DOI: 10.3109/00207459408987241
|View full text |Cite
|
Sign up to set email alerts
|

Brain Potentials from Dyslexic Children Recorded During Short-Term Memory Tasks

Abstract: Event Related Potentials (ERPs) from thirty children (9-13 years old); fourteen of whom were dyslexic and sixteen normal-reading controls, were recorded during the performance of a memory scanning task. Visually presented stimuli consisted of either digits (lexical) or unfamiliar (non-lexical) characters. The subjects had to indicate whether a probe stimulus was a member of a preceding memorized set, or not. The memorized sets included 1, 2 or 3 items. Performance accuracies were significantly lower and reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…In this case, Leppänen et al (1999) found an anomalous right lateralisation in infants at risk for dyslexia when faced with speech sounds which, according to the authors, is associated with poorer execution in subsequent linguistic measurements. In groups of older ages, other authors have also informed about greater right asymmetry with both linguistic and non-linguistic stimuli in subjects with reading problems (Barnea et al, 1994;Erez and Pratt, 1992;Landwehrmeyer et al, 1990).…”
Section: Ldnmentioning
confidence: 96%
“…In this case, Leppänen et al (1999) found an anomalous right lateralisation in infants at risk for dyslexia when faced with speech sounds which, according to the authors, is associated with poorer execution in subsequent linguistic measurements. In groups of older ages, other authors have also informed about greater right asymmetry with both linguistic and non-linguistic stimuli in subjects with reading problems (Barnea et al, 1994;Erez and Pratt, 1992;Landwehrmeyer et al, 1990).…”
Section: Ldnmentioning
confidence: 96%
“…With regard to working Executive Functions and Dyslexia memory which may be the most extensively studied aspect of executive functioning in children with dyslexia, a number of studies have demonstrated (Baddeley, 1982;Barnea et al, 1994;Brady et al, 1983;Brady et al, 1987;Breznitz, 1997;Chiappe et al, 2000;Hulme & Mackenzie, 1992;Jorm, 1979;Poblano et al, 2000;Swanson et al, 1989;Torgesen, 1977;Vargo et al, 1995;Willcutt et al, 2001) that verbal working memory in children with dyslexia is disturbed in comparison to non-dyslexic children. The results of the present study also indicate that children with dyslexia display impairments in tasks measuring verbal and figural working memory.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have made use of electrophysiological measures to examine working memory in dyslexics. One study (Barnea, Lamm, Epstein, & Pratt, 1994) found that the P300 amplitude was lower for lexical than non-lexical stimuli in dyslexic readers, and the opposite for skilled readers. Reaction time and accuracy were significantly longer and poorer among the dyslexics than the controls for both the lexical and non-lexical tasks.…”
Section: Introductionmentioning
confidence: 96%